PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI PADA BENGKEL MAJU JAYA - Adinata, Yustinus Christian; Rostianingsih, Silvia; Setiawan, Alexander (Jurnal Infra, 2013)
Maju Jaya is a workshop which sale of automotive products and services. Automotive products for sale are: tires, oil, spare parts and other accessories. Maju Jaya Workshop has administration problems such as transactions of purchases from supplier and sales to customer still uses manually processing, which has large risks.Due to background problems as mentioned above, then new application is developed and made by using Microsoft Visual Studio 2005.Net and Microsoft SQL Server 2005 software for its data storage. The application has some features, that are: data recording the purchases transactions from a supplier, data recording sales transactions, purchases reports, sales reports, reports payable, account receivables reports, stock reports, debt reminder, receivable reminder, stock reminders.From the result of system testing it can be concluded that the new system can solved the difficulties of Maju Jaya Workshop performance well. The application can record the transactions as described above that occured in Maju Jaya Workshop, this making the owner easier to checks the stock and transactions.